DEKONSTRUKSI FATWA MENGENAI LARANGAN BUNGA BANK (QIYAS VS ISTIHSAN) - Khotibul Umam (Veritas et Justitia, 2023)
Deconstruction is intended to serve as critique to the method of determining the prohibition status of bank interest, which is analogous to usury, as well as reconstructing the issue with other methods to produce a more implementable fatwa, especially in a pluralistic society. Normative legal research is carried out using a historical approach and a conceptual approach regarding usury and interest, as well as the methods and the rationale for the prohibition of both. Application of analogy (qiyas) can bring "unsatisfactory" results as a method of granting the legal status of bank interest in the context of a pluralistic society because this reasoning method is heavily focusing on 'illat (ratio legis, legal cause) and does not consider space, time, and circumstances involved. Meanwhile, the application of istihsan (juristic preference) is possible with justification for emergency (necessity), 'urf (custom) and maslahah (benefit), resulting in different legal status of bank interest that not all bank interest is haram. This provides convenience in its implementation within a pluralistic society.